Multigravida Dengan Hiperemesis Gravidarum - Heny Tri Andayani; Fonda Octarianingsih Shariff (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Multigravida with Hyperemesis Gravidarum (HEG). The patient came to the Emergency Room of Bintang Amin Hospital with G3P2A0 pregnancy 11 weeks with complaints of vomiting more than 5 times since morning accompanied by nausea. The patient said her body felt weak, dizzy, and had pain in the stomach. On physical examination, vital signs were obtained including blood pressure 95/27 mmHg, pulse 105 x / minute, respiratory rate 21x / minute, temperature 36.9°C, oxygen saturation 97%. On external examination, it was found that the abdomen was slightly convex, surgical scars (-), abnormalities (-) and palpation of the uterine fundus was not palpable, tenderness (-), mass (-). External examination was not performed. On hematology supporting examination, it was found that Hemoglobin and Leukocytes were within normal limits, while there was a decrease in erythrocytes of 4.1 ul and an increase in MCH 32 pg. Complete urine examination found leukocytes +++/(500), protein +/(50), and ketones ++++/(150). The diagnosis in this case is multigravida with Hyperemesis Gravidarum (HEG). Management in this patient is IVFD RL + 1amp neurobion 20 tpm, ondansetron 3x1 amp/iv, antacid syr 3x1c, Amoxicillin 3x1 tab. Keywords: First Trimester Complaints; Hiperemesis Gravidarum. Pasien datang ke Instalasi Gawat Darurat Rumah Sakit Bintang Amin dengan G3P2A0 hamil 11 minggu dengan keluhan muntah lebih dari 5x sejak pagi disertai mual. Pasien mengatakan badan terasa lemas, pusing, dan nyeri pada bagian perut. Pada pemeriksaan fisik didapatkan tanda-tanda vital diantaranya tekanan darah 95/27 mmHg, denyut nadi 105 x/menit, laju pernapasan 21x/menit, suhu 36,9°C, saturasi oksigen 97%. Pada pemeriksaan luar didapatkan inspeksi perut agak cembung, luka bekas operasi (-), kelainan (-) dan palpasi fundus uteri tidak teraba, nyeri tekan (-), massa (-). Pada pemeriksaan luar tidak dilakukan. Pada pemeriksaan penunjang hematologi didapatkan untuk Hemoglobin dan Leukosit dalam batas normal sedangkan terjadi penurunan pada eritrosit 4,1 ul dan peningkatan pada MCH 32 pg. Pada pemeriksaan urin lengkap didapatkan leukosit +++/ (500), protein +/ (50), dan keton ++++/ (150). Diagnosis pada kasus ini yaitu multigravida dengan Hiperemesis Gravidarum (HEG). Penatalaksanaan pada pasien ini adalah IVFD RL + 1amp neurobion 20 tpm, ondansentron 3x1 amp/iv, antasid syr 3x1c, Amoxicillin 3x1 tab. Kata Kunci: Hiperemesis Gravidarum; Keluhan Trimester Pertama.